Relative growth and sexual dimorphism in the hermit crab Clibanarius signatus Heller, 1861 (Anomura, Diogenidae) from the northern coast of the Persian Gulf, Iran - Ahmadi, Mahdieh; Noori, Ahmad; Kalvani Neitali, Bita; Antonio Amaro Pinheiro, Marcelo [UNESP] (Wiley, 2021)
The purpose of this study was to investigate the relative growth and sexual dimorphism in the hermit crab Clibanarius signatus. The evaluation was done with 955 specimens (494 males, 251 females, and 210 intersexes) captured in Persian Gulf (Iran) during January to December 2015. Animals were submitted to measurements related to weight (BW, total wet weight) and body size related to cephalic shield (SW, width; and SL, length) and propodus of both chelipeds (CPL, length; and CPW, width). Males were larger and heavier than females and intersexes. Both males and females showed a negative allometric growth for the SL–BW and SL–SW relationships, but a positive allometric growth to intersex specimens. To SL–CPL relationship, a negative allometric growth was confirmed in males and females independent of the laterality of the CPL, whereas a contrast was verified in intersexes, with a positive allometric growth occurred for both hands. To SL–CPW relationship, a negative allometric growth (b < 1) occurred in females, independent of the laterality of the CPW, while in males, a positive allometric pattern was confirmed. In intersexes, this relationship was positive except for the right CPW which was isometric. Sexual dimorphism was evident in Clibanarius signatus, with males being the largest and females the smallest specimens in the population.
Keywords: biometry; intersex; size; weight